Pembuatan Produk Inovasi Kembang Goyang Untuk Menjadi Produk Unggulan Dukuh Mulyomukti, Kelurahan Babat Jerawat, Surabaya - Anarta Cahyadiatma; Gideon Setyo Budiwitjaksono; Ni Nyoman Septi Artadiyani; Nimas Auralia Damayanti (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The micro, small and medium enterprise sector is one of the reliable sectors in the national economic map in Indonesia. Its ability to survive the threat of a global crisis become one of the sector's strengths. Therefore, the Indonesian government with Merdeka Campus program created one of the Community Service Program schemes to develop the creative economy and Small and Medium Micro Enterprises (MSMEs). In this service, it was carried out in the kelurahan Babat Jerawat, Surabaya, more specifically in Dukuh Mulyomukti. The development that carried out is to create and develop innovative products from students to become feature product. The implementation itself includes four stages, asking permission, surveys, program preparation and implementation. The activities carried out themselves provide training to MSME actors with the aim of providing human resources to be ready to move independently. The training started from training on SWOT analysis and making business plans, training on making logos and packaging, training on making product photos and cooking Kembang Goyang and finally branding using Instagram social media. The activity lasted for approximately one month was followed smoothly by the participants so that finally the product could be made and sold by the residents of Dukuh Mulyomukti themselves.